Brain-Based Learning Model to Improve Mathematical Reflective Thinking Ability in Trigonometry : An Experimental Study - Zakiyah, Siti; Muntazhimah, Muntazhimah (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the effect of applying the Brain-Based Learning (BBL) model on students' mathematical reflective thinking ability in trigonometric ratio material. The research employed a quasi-experimental method with a Nonequivalent Control Group Design, involving two 10th-grade classes at a public high school in Purwakarta,—one as the experimental class and the other as the control class. Data were collected through pretest and posttest using a mathematical reflective thinking ability test instrument. Since the data were not normally distributed, hypothesis testing was conducted using the Wilcoxon Signed-Rank and Mann-Whitney U tests. The Wilcoxon test showed a significance value of <0.01, indicating a significant improvement in the experimental class after the intervention. The Mann-Whitney test also revealed a significance value of <0.01, indicating a significant difference between the experimental and control classes. These results demonstrate that the BBL model significantly enhances students’ mathematical reflective thinking ability, particularly in mastering trigonometric ratio material.